Extensive prostatic calculi in alkaptonuria: An unusual manifestation of rare disease - Gaurav Sali; Appu Thomas; Ginil Kumar; Balagopalan Nair; Kalvampara Sanjeevan; Georgie Mathew; Kannan Nair (Asian Journal of Urology)
Extensive prostatic calculi in a young man should always elicit the suspicion of alkaptonuria. Although prostatic calculi are seen in chronic prostatitis, chronic pelvic pain syndrome and benign prostate hyperplasia, none of these have prostatic calculi or calcification as extensive as in alkaptonuria. A 36 years young man who had severed obstructive lower urinary tract symptoms with extensive prostatic calculi was found to be alkaptonuric on further evaluation.